2020
DOI: 10.1029/2020gl088659
|View full text |Cite
|
Sign up to set email alerts
|

Monsoon‐Induced Zonal Asymmetries in Moisture Transport Cause Anomalous Pacific Precipitation Minus Evaporation

Abstract: Basin-integrated precipitation minus evaporation (P − E) in the Pacific is near neutral while the Atlantic shows net evaporation. We link this P − E asymmetry to atmospheric moisture fluxes across the boundaries of the ocean drainage basins. Adopting an objective approach based on a comparison between actual fluxes and a zonally averaged circulation, we show that the asymmetry is dominated by moisture fluxes associated with the monthly mean flow at low latitudes rather than by differences in moisture fluxes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 39 publications
7
18
0
Order By: Relevance
“…Craig et al. (2020) suggested that the shapes of the southern hemisphere subtropical highs and the fractions of the ocean basins they occupy influences atmospheric moisture transport to and from the Southern Ocean basin. Partitioning Q n shows that northward QnSou ${Q}_{n}^{\mathit{Sou}}$ along 35°S is weakest on the Atlantic sector by about 22% compared to the Indian and Pacific sectors resulting in a strong net southward Q n .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Craig et al. (2020) suggested that the shapes of the southern hemisphere subtropical highs and the fractions of the ocean basins they occupy influences atmospheric moisture transport to and from the Southern Ocean basin. Partitioning Q n shows that northward QnSou ${Q}_{n}^{\mathit{Sou}}$ along 35°S is weakest on the Atlantic sector by about 22% compared to the Indian and Pacific sectors resulting in a strong net southward Q n .…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the North, the moisture import to the Arctic is dominated by the North Atlantic and North Pacific storm tracks (wedges of high Q n (x) across the widths of the basins in Figures 6d and 6f), demonstrating that Arctic precipitation is mostly associated with transient moisture fluxes (Craig et al, 2020;Gimeno et al, 2019;Vazquez et al, 2016). Across the Indian sector of the Arctic catchment boundary, northward Q n (x) is greatest around the Arabian peninsula corresponding with regions of high z BL and highly evaporative seas.…”
Section: Flux-weighted Densitymentioning
confidence: 99%
See 3 more Smart Citations